Predicting Tyrosine Kinase Inhibitor Treatment Response in Stage IV Lung Adenocarcinoma Patients With EGFR Mutation Using Model-Based Deep Transfer Learning - Hou, Runping; Li, Xiaoyang; Xiong, Junfeng; Shen, Tianle; Yu, Wen; Schwartz, Lawrence H.; Zhao, Binsheng; Zhao, Jun; Fu, Xiaolong (Frontiers in Oncology, 2021)
Background: For stage IV patients harboring EGFR mutations, there is a differential response to the first-line TKI treatment. We constructed three-dimensional convolutional neural networks (CNN) with deep transfer learning to stratify patients into subgroups with different response and progression risks. Materials and methods: From 2013 to 2017, 339 patients with EGFR mutation receiving first-line TKI treatment were included. Progression-free survival (PFS) time and progression patterns were confirmed by routine follow-up and restaging examinations. Patients were divided into two subgroups according to the median PFS (<=9 months, > 9 months). We developed a PFS prediction model and a progression pattern classification model using transfer learning from a pre-trained EGFR mutation classification 3D CNN. Clinical features were fused with the 3D CNN to build the final hybrid prediction model. The performance was quantified using area under receiver operating characteristic curve (AUC) and model performance was compared by AUCs with Delong test. Results: The PFS prediction CNN showed an AUC of 0.744 (95% CI: 0.645 to 0.843) in the independent validation set and the hybrid model of CNNs and clinical features showed an AUC of 0.771 (95% CI: 0.676 to 0.866), which are significantly better than clinical features-based model. (AUC: 0.624, P<0.01). The progression pattern prediction model showed an AUC of 0.762(95% CI: 0.643 to 0.882) and the hybrid model with clinical features showed an AUC of 0.794 (95% CI: 0.681, 0.908), which can provide compensate information for clinical features-based model. (AUC: 0.710, 95% CI: 0.582, 0.839). Conclusion: The CNN exhibits potential ability to stratify progression status in patients with EGFR mutation treated with first-line TKI, which might help make clinical decisions.